Rancang Bangun Aplikasi Simulasi Dekorasi Ruangan dengan Memanfaatkan Teknologi Markerless Augmented Reality - Putu Anggara Mahardika; I Made Arsa Suyadnya; Komang Oka Saputra (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2019)
Markerless Augmented Reality (AR) is a technology that combines two-dimensional or three-dimensional virtual objects into a real environment and then projects these virtual objects in real time without the need for a special marker. In this research, the Markerless AR application will be used to simulate room decoration with 3-dimensional objects. This research was built using the Java programming language and using supporting applications namely Android Studio and Wikitude library. Based on the results of testing with the Black-box method, the overall functionality of the application has run well, besides testing also uses the System Usability Scale (SUS) method by giving questionnaires to 20 application users. The results of the System Usability Scale (SUS) test obtained an average score of 73.13. In grouping the SUS percentile score, the value of 73.13 is in Class C, wherein this assessment the application is acceptable and can be used easily by the user.